Pengaruh Self Manajement Terhadap Prokrastinasi Akademik Pada Siswa Smpn 2 Cigombong Kelas VII: The Influence of Self-Management on Academic Procrastination in Grade VII Students of Smpn 2 Cigombong - Abdul Latif Ar Rasyid; Rusdi Kasman; Noor Isna Alfaien (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Self-management is an individual behavior management aimed at directing and controlling himself in order to achieve independence and make life productive.Due to the problems that often occur in the school environment,students behave negatively during teaching and learning activities such as students who like to stall for time, miss attendance, avoid difficulties and feel they have plenty of time to do a job. Students who often procrastinate in doing a job can be said to be people who do procrastination. academic procrastination if not prevented for a long time will have a broad negative impact, including unfinished work, unsatisfactory results, worry and despair in oneself, and lowering self-confidence in students. Therefore, self management is used to reduce the level of academic procrastination behavior experienced by students. The purpose of the study was to determine the magnitude of the effect of Self-management on Academic Procrastination of seventh grade students at SMPN 2 Cigombong school. This type of research method is quantitative adjective korelasional. With a population of 320 and taken for a sample of 76 students, with Random Sampling sampling technique. The data collection tools used in this study used a questionnaire from the Self-Management scale, and the Academic Procrastination scale. The results of this study indicate that the level of Self- Management and Academic Procrastination is in the Moderate category. Based on the results of the simple linear regression test, it can be concluded that there is an influence between self-management on academic procrastination with a significance value level of 0.000 <0.05 and the percentage of the influence of self-management on academic procrastination is 3.83%.